1991
DOI: 10.1111/j.1399-3054.1991.tb01713.x
|View full text |Cite
|
Sign up to set email alerts
|

Polyamines and ethylene in the removal of embryonal dormancy in apple seeds

Abstract: Putrescine (Put), spermidine (Spd) and spermine (Spm) were found in seeds of apple (Malus domestica Borkh. cv. Antonovka), in amounts that increased in the order given. The levels slowly decreased during 30 days of stratification. Exogenous polyamines (PAs) affected germination of isolated embryos in a way dependent on the type of polyamine, its concentration, and the state of the embryo dormancy. The effect of Put and Spd on germination was stimulatory, while that of Spm was inhibitory. Stimulation of germina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
2

Year Published

1994
1994
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 19 publications
3
13
2
Order By: Relevance
“…There are controversial reports on the effects of PAs on germination and seedling growth under both normal (Mirza and Bagni 1991;Sinska and Lewandowska 1991) and saline (Prakash and Prathapasenan 1988;Tıpırdamaz et al 1994;Chattopadhayay et al 2002) conditions. Some researchers have argued that PAs prevent germination ) even in normal conditions and some also have argued that they do not have any effect (Palavan-Ü nsal 1987).…”
Section: Discussionmentioning
confidence: 97%
“…There are controversial reports on the effects of PAs on germination and seedling growth under both normal (Mirza and Bagni 1991;Sinska and Lewandowska 1991) and saline (Prakash and Prathapasenan 1988;Tıpırdamaz et al 1994;Chattopadhayay et al 2002) conditions. Some researchers have argued that PAs prevent germination ) even in normal conditions and some also have argued that they do not have any effect (Palavan-Ü nsal 1987).…”
Section: Discussionmentioning
confidence: 97%
“…Our earlier research on dormancy breaking and germination of Norway maple seeds showed that exogenous spermine stimulates these processes by activation elongation factor 1 (Twardowski and Szczotka 1989). Sifiska and Lewandowska (1991 ) demonstrated that germination of Malus domestica embryos is altered by the presence of PAs in the medium during stratification of the seeds. In beech seeds treated with exogenous PAs, stimulation of protein synthesis was observed.…”
Section: Discussionmentioning
confidence: 98%
“…Exogenous PAs affected germination of isolated embryos in a way dependent on the type of polyamine, its concentration, and the state of the embryo dormancy. The effect of Put and Spd on the germination of apple seed was stimulatory, while that of Spm was inhibitory (Sińska and Lewandowska 1991). There is now conclusive evidence that PAs accumulate in plants and are involved in their protection against various environmental stresses (Bouchereau et al 1999;He et al 2002;Farooq et al 2009a).…”
Section: Introductionmentioning
confidence: 96%